2000
DOI: 10.1054/bjoc.1999.0963
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a founder BRCA2 mutation in Sardinia

Abstract: Breast cancer is the most common malignancy in women, with an incidence that varies between 40 and 90 per 100 000 (standardized rate) worldwide. Breast cancer is the most frequent female tumour in Italy, representing about 25% of all female tumours as reported in Italian registries (Zanetti et al, 1997).A positive family history is known to be a high risk factor for developing the disease: 5-10% of all breast cancers arise in individuals carrying a germline mutation and are usually considered hereditary forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 17 publications
2
31
1
1
Order By: Relevance
“…The proportion of breast cancer families attributable to BRCA1 and BRCA2 mutations in this study is relatively lower when compared to many studies [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. However, the finding of only one of seventeen breast families with BRCA1 mutations is less than has been reported elsewhere.…”
Section: Cancer Therapy and Oncology International Journal Discussioncontrasting
confidence: 82%
“…The proportion of breast cancer families attributable to BRCA1 and BRCA2 mutations in this study is relatively lower when compared to many studies [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. However, the finding of only one of seventeen breast families with BRCA1 mutations is less than has been reported elsewhere.…”
Section: Cancer Therapy and Oncology International Journal Discussioncontrasting
confidence: 82%
“…Most of these mutations (13 mutations; 86.7%) were found in BRCA2, and only small numbers (2 mutations; 13.3%) were found in BRCA1. The mutation BRCA2-8765delAG, which we described previously as a frameshift mutation with founder effect in North Sardinia, 29 remained the only recurrent mutation among families from our series (prevalence, 12 of 102 families; 11.8%) ( Table 2). The distribution of familial members carrying the BRCA2-8765delAG variation and originating from different villages in North Sardinia further confirmed the founder effect of this germline mutation in such a geographic area (Fig.…”
Section: Resultsmentioning
confidence: 64%
“…30 Haplotype analysis of some Sardinian and French-Canadian families, as we reported previously, 29 demonstrated that the BRCA2-8765delAG mutation is associated with different haplotypes in 2 such populations (DNA samples of French-Canadian BRCA2-8765delAG carriers kindly were provided by Dr. Tonin). These results support the hypothesis that the AG-rich sequence in which the BRCA2-8765delAG mutation occurs may be a mutational hot-spot.…”
Section: Discussionmentioning
confidence: 69%
“…Genomic DNA was extracted from formalin-fixed paraffin-embedded samples after microdissection separating tumour tissue from adjacent stroma by light microscopy. DNA was isolated according to previously described protocols (Pisano et al, 2000). Control DNA was obtained from normal adjacent skin of the corresponding patients.…”
Section: Tissue Samples and Dna Extractionmentioning
confidence: 99%